Method of automatic extraction of paradigmatic relations between the concepts of a glossary - Петрасова, Светлана Валентиновна; Кочуева, Зоя Анатольевна; Хайрова, Нина Феликсовна (Bulletin of National Technical University "KhPI". Series: System Analysis, Control and Information Technologies, 2013)
In this article, the method of the automatic identification of semantic paradigmatic relations between concepts of the glossary has been considered. Patterns of lexical sets have been used for the identification of concepts’ relations of belonging to the class, hypernymy, hyponymy and myronymy. A measure of the semantic proximity has been determined for the identification of the semantic equivalence. The developed software implementation has been described and the quality indexes experimentally determined have been produced.